THE DYNAMICS OF KEBOAN SUKODONO TRADITION IN ALIYAN VILLAGE OF BANYUWANGI - Rohmah, St. Shabibatul; Mahfud, Mahfud; Kusuma, Surya Martha (Nusantara Hasana Berdikari, 2021)
Tradition tradition Keboan tradition is a tradition of inheritance that aims to clean the village, held in the month of Shura (Javanese calendar) as well as a medium to ask for help to be kept away from all the dangers that are not cooled. The issues studied are: 1) History Keboan, 2) Dynamics of customs tradition keboan Sukodono, 3) Stages in the implementation of Sukodoo keboan and 4) The value contained in the customary tradition. The results explain that the history keboan originated from the occurrence of unrest in the community where they get a strange disease that deadly. Tradition custom keboan Sukodono experiencing some changes due to politics and terpangkasnya rituals that are considered sacred for traditional leaders. The course of ritual procession begins to prepare food, selamatan village, after that many people possessed by ancestral spirits. The values ​​contained include the value of religion, entertainment, social togetherness and economic value.